Perancangan Interior Atmosphere Executive Lounge and Night Club di Surabaya - Herryanto, Daniel Ryan (Intra, 2014)
Citizensâ need of night leisure facility or night entertainment grows larger as the city itself progress in development. Nightclub, as one of the best-known and fast-growing example of night entertainment facility, is capable of answering the needs by giving the citizens a place in which they can release their tension from their daily routines and have fun for a while. Due to the rapid growing of nightclub in the night entertainment industry, it is very crucial for a designer or a developer to imbue a specific theme in a nightclub to ensure the ability to compete from similar night entertainment facility by giving the customer a different experience and atmosphere depending on the installed theme that may be applied and linked together on interior design, exterior design, and furniture design.